2018
DOI: 10.1111/jgs.15659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Opioid Prescribing, Overdose, and Mortality in Massachusetts, 2011 to 2015

Abstract: Background/Objectives: Potentially inappropriate opioid prescribing (PIP) may contribute to risk for fatal opioid overdose among older adults (age 50+). Our objective was to examine the effect of age on the likelihood of PIP exposure, as well as the effect of PIP exposure on adverse outcomes. Design: Retrospective cohort study Setting: Data from multiple state agencies in Massachusetts, 2011–2015 Participants: Over 3 million adult Massachusetts residents (3,078,163) who received at least one prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…The association of prescription opioid use, either medically or nonmedically, with subsequent opioid use has been well-described ( Grau et al, 2007 ; Lankenau et al, 2012 ; Mars et al, 2014 ; Rose et al, 2018 ). Factors associated with prescription opioid initiation, misuse, and overdose include potentially inappropriate opioid prescribing, such as multiple prescribers and co-prescription of opioids and benzodiazepines ( Rose et al, 2019 ; Sun et al, 2017 ). The role of the over-prescription of opioids as a feature of the urban risk environment has also been well-studied ( Ciccarone, 2018 ; Grau et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of prescription opioid use, either medically or nonmedically, with subsequent opioid use has been well-described ( Grau et al, 2007 ; Lankenau et al, 2012 ; Mars et al, 2014 ; Rose et al, 2018 ). Factors associated with prescription opioid initiation, misuse, and overdose include potentially inappropriate opioid prescribing, such as multiple prescribers and co-prescription of opioids and benzodiazepines ( Rose et al, 2019 ; Sun et al, 2017 ). The role of the over-prescription of opioids as a feature of the urban risk environment has also been well-studied ( Ciccarone, 2018 ; Grau et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the over-prescription of opioids as a feature of the urban risk environment has also been well-studied ( Ciccarone, 2018 ; Grau et al, 2007 ). Strong associations exist among inappropriate opioid prescribing, risk for overdose, and all-cause mortality ( Rose et al, 2018 , 2019 ; Stopka et al, 2017 ). Additionally, abrupt discontinuation of opioid prescriptions and inadequate tapering is known to lead to transitions to heroin and fentanyl use and elevated overdose risk ( Brady et al, 2015 ; Mars et al, 2014 ; Somerville et al, 2017 ; Mark and Parish, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Described in detail elsewhere [13][14][15], innovative solutions were used to protect data privacy, even beyond the standards set by federal and state law, and to create mechanisms for data sharing. Studies conducted with PHD data over the past five years have been critical to documenting the causes and consequences of the opioid epidemic [7,[17][18][19][20][21][22][23][24].The PHD Warehouse is a groundbreaking essential resource for conducting data-driven public health surveillance, resource allocation, intervention planning, and innovative research [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…19 A study using data from the 2009-2014 National Survey on Drug Use and Health (NSDUH) found that a medical source for misused opioids was more common among older adults than younger adults. 14 Given that older adults are more likely to be co-prescribed opioids and benzodiazepines than younger adults 20 and that benzodiazepine use elevates opioid overdose risk, 21 older adults may experience heightened consequences from opioid misuse. While heroin accounts for more hospitalizations and deaths among younger adults, prescription opioids overwhelmingly account for hospitalizations and death among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…While heroin accounts for more hospitalizations and deaths among younger adults, prescription opioids overwhelmingly account for hospitalizations and death among older adults. 20,22 The objective of this study is to further characterize the extent to which opioid misuse presents differently across age groups, particularly older adults. Using the 2015-2017 NSDUH data on individuals with past-year prescription opioid misuse, we examine how prescription opioid source (i.e., medical, social, and illicit/other) and motives for misuse vary across age groups.…”
Section: Introductionmentioning
confidence: 99%